The Role of Uncertainty in the Experiences of Nurses During the Covid-19 Pandemic: A Phenomenological Study. Issue 2 (June 2021) - Nelson, Heather; Hubbard Murdoch, Natasha; Norman, Kasandra
Background: The novel coronavirus (Covid-19) has spread quickly to all corners of the globe and caused high rates of morbidity and mortality. Nurses have been at the centre of this experience managing the outbreak through direct bedside care, managing hospital units, providing Covid-19 testing, and contact tracing. Purpose: The aim of this article is to examine the role that nurses played in the early stages of the Covid-19 pandemic through the voices of the participants. Methods: Using a phenomenological methodology thirty-one interviews were completed via phone and thematic analysis was completed. Results: The major themes that emerged from this phenomenological study were: emotional challenges, uncertainty, and protective factors. Emotional challenges included, stress, anxiety, exhaustion, frustration, guilt, and loneliness. These challenges were magnified by uncertainty through leadership and communication challenges, needs of the pandemic versus needs of the patient, and Covid-19 and best practice. In this study, emotional challenges were mitigated by the protective factors of: education, ability to contribute, team cohesiveness, and community support. Conclusions: Nurses are challenged during this time but by limiting uncertainty and providing protective factors, nurses can be less affected by emotional challenges and able to provide nursing care and manage the outbreak effectively.